ECONOMIC FREEDOM AND INDIVIDUAL WELFARE IN PERU - Rodríguez Cairo, Vladimir (2016)
The research made possible to explain why economic freedom was a factor that contributed to improving individual well-being in Peru during the period 1970-2014. Based on this objective, a descriptive analysis was performed on the relationship between the variables, plus two approximations were used based on the inferential analysis: Spearman correlation coefficient and Ordinary Least Squares estimate.Thus, the main results show that there is a relationship between the Index of Economic Freedom and the Gross Domestic Product per capita, and the strong degree of this relationship. In addition, it was found that the sense of the relationship is positive and statistically significant.In this way, it was concluded that economic freedom is one of the factors that influenced individual welfare, and consequently, general well-being of the population. However, economic freedom is necessary but not a sufficient condition for determining well-being. Therefore, among the main aspects of economic freedom in Peru we found improvements in the regulation of credit, labor and business, international trade and financial strength, as well as more modest advances in the legal structure and size of government.